2019
DOI: 10.1111/jep.13147
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and burnout: A multicentre comparative study between residents and specialists

Abstract: Rationale, Aims, and Objectives:The prevalence of burnout among medical doctors and its negative effect on empathy can influence therapeutic success. The aim of this study was to compare the levels of empathy and burnout between residents and specialists as well as to study the correlation between empathy and burnout. Methods: This is an exploratory study of a convenience sample of 104 doctors who work in health institutions in Greater Lisbon area in Portugal, covering central hospitals, district hospitals, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 33 publications
(37 reference statements)
1
28
0
Order By: Relevance
“…Conversely, personal problems predicted lower ECRC 87 , 131 , 146 , 148 . Good subjective health predicted greater ECRC 87 , 107 , 131 , while signs of fatigue 38 , 87 , 93 , 145 , 146 , 149 , 153 , 159 , burnout 65 , 84 , 93 , 124 , 147 , 148 , 158 , 160 166 , and stress 98 , 131 , 148 , 158 , 160 , 167 tended to associated with ECRC negatively. The evidence regarding the effects of compassion fatigue on ECRC 52 , 65 , 154 or evidence related to mental health (i.e., mental well-being and anxiety) in relation to ECRC 50 , 77 or was too scarce and/or unclear.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Conversely, personal problems predicted lower ECRC 87 , 131 , 146 , 148 . Good subjective health predicted greater ECRC 87 , 107 , 131 , while signs of fatigue 38 , 87 , 93 , 145 , 146 , 149 , 153 , 159 , burnout 65 , 84 , 93 , 124 , 147 , 148 , 158 , 160 166 , and stress 98 , 131 , 148 , 158 , 160 , 167 tended to associated with ECRC negatively. The evidence regarding the effects of compassion fatigue on ECRC 52 , 65 , 154 or evidence related to mental health (i.e., mental well-being and anxiety) in relation to ECRC 50 , 77 or was too scarce and/or unclear.…”
Section: Resultsmentioning
confidence: 94%
“…Second to professional characteristics, a high proportion of mostly quantitative studies examined socio-demographic factors. Female gender was associated with higher ECRC in numerous studies 41 , 43 , 45 , 47 , 49 , 52 , 55 , 58 , 61 , 64 , 81 83 , 92 , 94 , 95 , 99 , 101 , 103 , 108 , 113 117 but a comparable number showed no gender effect 39 , 48 , 50 , 51 , 54 , 60 , 72 , 74 , 76 – 80 , 84 , 86 , 96 , 105 , 106 , 116 , 118 121 ; three studies reported males as more compassionate 53 , 111 , 112 . Evidence regarding age was similarly conflicted 39 41 , 43 , 47 , 49 – 51 , 54 , 55 , 58 , 60 , 72 , 77 , 80 , 82 , 84 , 86 , 95 , 99 , 106 ...…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The high levels of burnout during residency have detrimental personal consequences such as substance abuse (Lebensohn et al 2013) and suicidal thoughts (van der Heijden et al 2008). Furthermore, when suffering from burnout resident physicians commit more medical errors (Baer et al 2017;Prins et al 2009), express lower empathy (Ferreira et al 2020;Park et al 2016), and adhere less to practice and safety standards (de Oliveira et al 2013).…”
mentioning
confidence: 99%
“…On the other hand, it should not be forgotten that the high empathic skills of midwives and other personnel may lead to compassion fatigue, secondary stress and compassion fatigue over time 34,35 . Çankaya et al (2020) 36 argued that the high empathic approach of some midwives who witnessed traumatic births caused secondary trauma.…”
Section: Discussionmentioning
confidence: 99%